Soil chemical and physical properties modified by weed control and organic fertilization in an apple orchard - Espanhol, Gilmar Luiz; Albuquerque, Jackson Adriano; Mafra, Álvaro Luiz; Nuernberg, Névio João; Nava, Gilberto (Revista de Ciências Agroveterinárias, 2007)
The application of poultry litter to the soil and its effects on soil physical and chemical properties, as well as on apple fruit productivity, has been poorly studied. This study was carried out in a commercial apple orchard established in 1985, in São Joaquim, SC, southern Brazil, using Fuji cv. on Marubakaido rootstock. Two methods of weed control were applied in 1997, one chemical with herbicide and another mechanical with eight mowing, associated to four doses of poultry litter (0, 5, 10 e 20 Mg ha-1), with the objective of evaluating changes in chemical and physical properties of an Inceptisol. The experimental design was a randomized block, with split-split-plot design and four replications. Soil samples were collected at three different layers and analyzed for Ca2+, Mg2+, K+, Na+, Al3+, water pH, nitrate, ammonium, organic carbon, aggregate stability, total porosity and bulk density. The mechanical weed control with mowing increased Mg2+, organic carbon and water pH values, and reduced Al saturation in comparison with the weed control using herbicide. The addition of poultry litter, due to its chemical composition, increased Ca+, Na+, K+, and sum of bases status, reduced soil acidity, but did not change soil aggregate stability, total porosity and bulk density. Therefore, the mechanical weed control, associated to the fertilization with poultry litter, is a good alternative to improve chemical properties of these acidic and nutrient deficient soils, helping to increase apple productivity, especially in agro-ecological production systems.